A DFT study on the cyclization-degradation mechanism for phenylmethylsiloxanes in thermal vacuum. (January 2022) - Ding, Yunqiao; Lu, Haifeng; Mou, Qiuhong; Peng, Dan; Yu, MengTing; Wu, Yanhong
Highlights: Whether for polyphenylmethylsiloxanes or for polydimethylsiloxanes, the cyclization degradation in thermal vaccum undergoes the four-memberred cyclic transition state, which is bound to determine that the flexibility of backbone plays a decisive role in the activation energy of degradation. The effect of the end group on the activation energy of depolymerization is little, and vanishes as the growth of the main chain. If the end group has not a great influence on the flexibility of the backbone, it is less vulnerable to the activation energy of backbone depolymerization. Based on the above two points, present result confirms that the hydroxyl terminal structure confers less stability than trimethylsiloxyl terminal one in the polymethylphenylsiloxanes. The principal effect of hydroxyl end-groups is to assist in the cleavage of Si-Ph or Si-C bonds in the way of the hydrogen abstraction. Abstract: A series of DFT calculations has been performed on the cyclization-degradation mechanisms of phenylmethylsiloxanes in a thermal vacuum. Like dimethylsiloxanes, a four-membered cyclic motif is identified for all transition states. The flexibility of the backbone is a precondition for the back-biting reaction. The phenylmethylsiloxanes confer more stability than the dimethylsiloxanes because the replacement of methyl by phenyl reduces the flexibility of the backbone. The activation energy is mainly determined by the total energy effect in the process of bonds' formation and scission. The depolymerization of the main chain for the phenylmethylsiloxanes is higher in the energy barrier than that for the dimethylsiloxanes by about 14.38 kcal/mol. The cyclization degradation mechanism of them little differs intrinsically. The effect of the end group on the activation energy of the depolymerization reduces rapidly as the main chain lengthens. Whether in phenylmethylsiloxanes or in dimethylsiloxanes, the effect of hydroxyl end-groups is to assist in the cleavage of Si-C bonds in the way of the hydrogen abstraction, hence, the replacement of the trimethylsilyl terminal group by the dimethylhydroxylsilyl group should decrease the thermal stability of siloxanes. The phenylmethylsiloxanes show slightly higher activation energy of intramolecular hydrogen abstraction than the dimethylsiloxanes, because the methyl has a stronger reducibility than the phenyl.